Teachers' Personal Theories Regarding the Management of Ethnocultural Diversity in General and Intercultural Primary Schools - Θεοδοσιάδου, Κυριακή; Παπαδοπούλου, Βασιλική (Education Sciences, 2023)
The phenomenon of migration has transformed the Greek school into a multiethnic environment, reshaping the issues raised about good practices and the role the teacher plays in the smooth integration of diverse cultures, not only in the school but also in the wider Greek society. This paper examines how cultural diversity is managed in Greek primary schools by focusing on the content of teachers’ personal theories, which guide their actions, although those actions to a large extent show lack of consciousness. The research also compares personal theories and practices between teachers working in general and intercultural primary schools. The participants are 20 primary school teachers in the Regional Unit of Pella and Thessaloniki who teach in multicultural classes. Qualitative research methods were used, through a variety of tools, such as teaching observation, in-depth interviews and text analysis. The findings show the tendency of teachers to use assimilative practices with minimal exceptions of teachers from intercultural schools.